Pengaruh Pemahaman Akuntansi dan Penerapan SAK EMKM Terhadap Kualitas Laporan Keuangan di Kecamatan Medan Polonia - Salsa Nurmala; Heny Triastuti Kurnia Ningsih; Shofwan Andri (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2026)
This study aims to examine the effect of accounting understanding and training on the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) on the quality of financial statements of Micro, Small, and Medium Enterprises (MSMEs) in Medan Polonia District. The study population comprised all MSMEs operating in the district. A total of 50 MSMEs were selected as the sample using the total sampling (census) method, in which all members of the population were included as respondents. This research employed a quantitative approach using multiple linear regression analysis, including the t-test, F-test, and coefficient of determination (R²) to examine the effects of the independent variables on the dependent variable. The findings indicate that accounting understanding has a positive and significant effect on the quality of MSMEs' financial statements. In addition, training on the implementation of SAK EMKM also has a positive and significant effect on financial statement quality. These findings suggest that improving accounting competence and providing continuous SAK EMKM training play an important role in producing higher-quality, reliable financial statements that comply with applicable accounting standards.